Anglo intrusion on the old Sangre de Cristo Land Grant - Smith, Jeffrey S. (My University, 2010)
Positioned on the northern edge of the Hispano homeland, the southern portion of the old Sangre de Cristo Land Grant (present-day Costilla County, Colorado) provides an interesting empirical study of cultural change. After economically displacing Spanish-American residents from villages throughout the homeland's core, incoming Anglos have adopted the region's rich Spanish culture as their own. On the homeland's periphery, however, the cultural traditions of Hispanos and Anglos have been, for the most part, at odds. Most resident Hispanos desire to maintain ties to their traditional past, while the younger generations embrace Anglo cultural norms. Considering the vital role it plays in the maintenance of culture, religion provides a window to the study area's modified cultural environment. In 1900 the population in this region was predominantly Catholic Hispano; by 1990 Protestant-dominated Anglos comprised a sizeable proportion of the population. Comparisons are made between traditional Hispano and Anglo-influenced religious landscapes. Changes in church affiliation, the distribution of active Penitente moradas, and the characteristics of community cemeteries demonstrate ongoing cultural change. Geographically isolated communities, where Anglo intrusion is limited, retain their strong Hispano cultural integrity.
Keywords: Religious landscape; Cultural change; Hispano homeland; Colorado; New Mexico